2021
DOI: 10.1111/tpj.15512
|View full text |Cite
|
Sign up to set email alerts
|

A tomato NAC transcription factor, SlNAM1, positively regulates ethylene biosynthesis and the onset of tomato fruit ripening

Abstract: SUMMARY Fruit ripening in tomato (Solanum lycopersicum) is the result of selective expression of ripening‐related genes, which are regulated by transcription factors (TFs). The NAC (NAM, ATAF1/2, and CUC2) TF family is one of the largest families of plant‐specific TFs and members are involved in a variety of plant physiological activities, including fruit ripening. Fruit ripening‐associated NAC TFs studied in tomato to date include NAC‐NOR (non‐ripening), SlNOR‐like1 (non‐ripening like1), SlNAC1, and SlNAC4. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 104 publications
0
33
0
Order By: Relevance
“…For instance, NAC‐NOR binds to the promoter of SlPL and activates its expression, thereby regulating fruit softening (Gao et al, 2020). SlNAC4 binds to the promoters of SlCEL2 and SlEXP1 , which encode cell wall degrading enzymes, to promote tomato fruit softening (Gao et al, 2021). In vitro and in vivo analyses showed that NOR‐like1 binds to the promoters of SlPG2a, SlPL, SlCEL2 , and SlEXP1 , which encode cell wall‐modifying enzymes, to activate their expression and promote fruit softening (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, NAC‐NOR binds to the promoter of SlPL and activates its expression, thereby regulating fruit softening (Gao et al, 2020). SlNAC4 binds to the promoters of SlCEL2 and SlEXP1 , which encode cell wall degrading enzymes, to promote tomato fruit softening (Gao et al, 2021). In vitro and in vivo analyses showed that NOR‐like1 binds to the promoters of SlPG2a, SlPL, SlCEL2 , and SlEXP1 , which encode cell wall‐modifying enzymes, to activate their expression and promote fruit softening (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAC TFs participate in the regulation of fleshy fruit ripening-associated processes in banana (Shan et al, 2012), tomato (Kou et al, 2018), peach (Zhou et al, 2015), melon (Wang et al, 2022), apple (Migicovsky et al, 2021), and strawberry (Martín-Pizarro et al, 2021). For instance, NOR (non-ripening), a NAC TF, regulates tomato fruit ripening (Gao et al, 2020) alongside other NAC family TFs, including SlNAC1, SlNAC4, NOR-like1, and SlNAM1 (Gao et al, 2018(Gao et al, , 2021Kou et al, 2018;Ma et al, 2014). In apple, the NOR ortholog MdNAC18.1 is thought to be a major determinant of fruit softening and harvest date (Migicovsky et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Gao et al [70] identified a new NAC TF, SlNAM1, in tomato and obtained homozygous gene-edited mutants of SlNAM1 using CRISPR/Cas9 technology. It was found that the timing of the ethylene peak and ripening onset in SlNAM1 mutant fruits were both delayed, whereas they were advanced in SlNAM1-overexpressing fruit.…”
Section: Nac Tfs Are Involved In Plant Hormone Biosynthesis and Signa...mentioning
confidence: 99%